Suitable electric generator for pico-hydro power plant in ambato–huachi–pelileo water irrigation channel - Cumbajín, Myriam (2020)
We present the analysis of the selection of electric generator suitable for Pico-Hydro Power Plant in the Ambato-Huachi-Pelileo irrigation channel in Ecuador. For which a meticulous literary review has been carried out about the main characteristics of the Pico-Hydro Power Plant as it is the height, the hydric resource, the turbine and the generator. Considering the water resource, which in our case is provided by the Ambato-Huachi-Pelileo irrigation channel, the parameters of low height and slow speed have been taken around 1.6 m3/s, which has allowed us to analyze the generator suitable for the required Pico-Hydro Power Plant. Therefore, the study conducted has allowed us to conclude that the electric generator suitable for the Pico-Hydro Power Plant in the Ambato-Huachi-Pelileo irrigation channel is a radial flux permanent magnet generator that is capable of providing sufficient electrical power with a simple structure, low revolutions, and high efficiency. Also, a Matlab simulation was developed in order to predict the power which is capable of provide the radial flux permanent magnet generator which in this case is 3.8 KW. This work aims to provide several benefits to the society bordering the irrigation channel, such as generating energy for self-consumption as a contribution to the lighting of the channel at no cost to the public in order that it is not dangerous for the passers at night and providing the ability for maintenance works at any time. © Springer Nature Switzerland AG 2020.